Ethical Education and Shaping Character of Youngsters in the Contetxt of Training the Future Teachers of Elementary and Secondary Schools in the Czech Republic - Krakora, Pavel (Civilia, 2016)
Text deals with the ethics education a shaping character in the context of the Czech Republic. The attention is paid to relation pupil-teacher-school-family, in addition to that theoretical foundations of given problems and its application in educational process. On example of Department of Social Sciences of Faculty of Education of Palacky University Olomouc is demonstrated concrete form of ethics teaching for future teachers including questions, which in given context relating to shaping character (children, youth, teachers). This theme is topical for today's society not only in the Czech Republic, but also in broader context exceeding boarders of individual states.
Keywords: Ethics; Shaping Character; Education; Youth; Teachers; School; Family; Morality; Theory; Practice; Czech Republic; Department of Social Science; Faculty of Education; Palacky University Olomouc